Cytotoxic effect of Cousinia verbascifolia Bunge against OVCAR-3 and HT-29 cancer cells - Sajjadi Seyed Ebrahim; Ghanadian Mustafa; Haghighi Mehrangiz; Mouhebat Leili (Shahrekord University of Medical Sciences, 2015)
Introduction: Little information is available about phytochemical and biological properties of Cousinia genus. In a primary study, seven Cousinia species including C. verbascifolia showed cytotoxic activity ranged between 18.4 ± 0.59 to 87.9 ± 0.58 μg/mL. To the best of our knowledge, no other biological studies have been conducted on this plant. Therefore, in this study the cytotoxic effect of Cousinia verbascifolia Bunge against OVCAR-3 and HT-29 cancer cells was evaluated. Methods: Filtration and in vacuo concentration of methanol extract resulted in a green gum which was subjected on reverse column chromatography. Semi polar fraction (41.3 g) eluted with water: methanol (20:80), was then subjected on a silica gel column chromatography using hexane/acetone and resulted in 11 fractions. Finally, cytotoxic activities against ovarian and colon cancer cells were determined at a wavelength of 570 nm by Matrix metalloproteinase protein (MTT) standard method. Results: None of the fractions showed highly cytotoxic activity. Based on NCI, fractions Fr. 1, Fr. 2, Fr. 4, Fr. 5, Fr. 6, Fr. 8 and Fr. 10 showed moderately cytotoxicity with IC50 values ranged between 119 to 190 μg/mL against OVCAR-3 cells. Fractions Fr. 1, Fr. 2, Fr. 6, Fr. 7 and Fr. 8 showed moderately cytotoxic activity ranged between 118 to 194 μg/mL against HT-29 cells. Fr. 10 and Fr. 11 showed no cytotoxic activity. Conclusion: Due to the inhibitory properties of extract and its fractions on cancer cells, identification of responsible compounds possessing cytotoxic effects for generating possible new approach in medicinal chemistry are recommended.